(untitled) (Al-Academy, 2022)
Fabric design is one of the arts in which humans participate functionally and aesthetically. Researching its design aspects is an important goal, especially after taking technical developments to cover many of its fields. Modern designs emphasize the importance of preparing designs and implementing them according to the child’s ability, inclinations and desires (mental, psychological and emotional). ), as the child is the real focus of the design idea, and the designer has paid most of his attention to the requirements and needs of this stage (childhood stage) because of its importance in the life of society, as he focused his attention on implementing designs that could achieve stability and stability in the child’s psyche through shapes Accordingly, the current research was based on the imposition of the following question: What are the aesthetic values and design foundations in the designs of fabrics and children’s fashion?The research also dealt with three sections, the first topic included the methodological framework in posing the problem, its importance and objectives as well as the definition of the most important terms, and the second topic included The theoretical framework, which included the following topics: First: Aesthetic value and its perception among children and its role in the designs of fabrics and fashion Second: The foundations of art Mimeh for children’s fabric designs. As for the third topic, it included the research procedures to reach the objectives of the research, and it relied on the analytical description method, then the most important results and recommendations were included, and finally the sources and references were confirmed.